Predictors of unstructured antiretroviral treatment interruption and resumption among HIV‐positive individuals in Canada. Issue 2 (1st September 2014) - Samji, H; Taha, TE; Moore, D; Burchell, AN; Cescon, A; Cooper, C; Raboud, JM; Klein, MB; Loutfy, MR; Machouf, N; Tsoukas, CM; Montaner, JSG; et al.
<x xml:space="preserve">Abstract</x> Objectives Sustained optimal use of combination antiretroviral therapy (cART) has been shown to decrease morbidity, mortality and HIV transmission. However, incomplete adherence and treatment interruption (TI) remain challenges to the full realization of the promise of cART. We estimated trends and predictors of treatment interruption and resumption among individuals in the Canadian Observational Cohort (CANOC) collaboration. Methods cART‐naïve individuals ≥ 18 years of age who initiated cART between 2000 and 2011 were included in the study. We defined TIs as ≥ 90 consecutive days off cART. We used descriptive analyses to study TI trends over time and Cox regression to identify factors predicting time to first TI and time to treatment resumption after a first TI. Results A total of 7633 participants were eligible for inclusion in the study, of whom 1860 (24.5%) experienced a TI. The prevalence of TI in the first calendar year of cART decreased by half over the study period. Our analyses highlighted a higher risk of TI among women [adjusted hazard ratio (aHR) 1.59; 95% confidence interval (CI) 1.33–1.92], younger individuals (aHR 1.27; 95% CI 1.15–1.37 per decade increase), earlier treatment initiators (CD4 count ≥ 350 vs. < 200 cells/μL: aHR 1.46; 95% CI 1.17–1.81), Aboriginal participants (aHR 1.67; 95% CI 1.27–2.20), injecting drug users (aHR 1.43; 95% CI 1.09–1.89) and users of zidovudine vs. tenofovir in the initial cART regimen (aHR 2.47; 95% CI 1.92–3.20). Conversely, factors predicting treatment resumption were male sex, older age, and a CD4 cell count < 200 cells/μL at cART initiation. Conclusions Despite significant improvements in cART since its advent, our results demonstrate that TIs remain relatively prevalent. Strategies to support continuous HIV treatment are needed to maximize the benefits of cART.